Factors Associated to Implant Use among Married Women of Reproductive Age in Banyuwangi - Firdawsyi Nuzula; Ni Putu Widarini; I Nyoman Mangku Karmaya (Universitas Udayana, 2015)
Background and purpose: The proportion of implant use at Tegalsari District of Banyuwangi has increased year by year until it reached 17% in 2013. This proportion was much higher than the national and provincial rates. This study aims to determine factors related to implant use among married women of reproductive age at Tegalsari District of Banyuwangi. Methods: This was a cross-sectional survey involving 198 married women of reproductive age who were using contraception at Tegalsari district. Data was collected by conducting interview in each respondent’s house using a structured questionnaire. Univariate analysis was conducted to determine frequency distribution of each variable, bivariate analysis using the chi-square test, and multivariate analysis was performed to determine factors that independently associated to the use of implant using logistic regression. Results: The proportion of implant use in women of reproductive age at Tegalsari District was 21.21%. Multivariate analysis indicated that the statistically significant factors associated with implant use were cultural value with adjusted OR=3.59 (95%CI: 1.44-8.94), knowledge on implant with adjusted OR=15.10 (95%CI: 3.44-74.40), role model with adjusted OR=3.43 (95%CI: 1.47-8.06) and information from health workers with adjusted OR=3.13 (95%CI: 1.16-8.44). Conclusion: Factors related to implant use among married women of reproductive age were supported cultural values, role model, good knowledge about implant and information from health workers.